Examination of the Earthquake (Samos Island) in Izmir (30.10.2020) by Using Cors-Tr GNSS Observations and InSAR Data - Pirti, Atinc; Hosbas, Ramazan Gursel; Yucel, Mehmet Ali (KOREAN SOCIETY OF CIVIL ENGINEERS-KSCE, 2023)
Izmir, which is one of the biggest cities of Turkey and has the extensive tectonic features of the Western Anatolia region, has been struck in recent years due to its high seismic activity. In particular, the south of Izmir is one of the regions that has high seismic activity in the city, which is constrained by major fault zones. The earthquake of magnitude of a Mw 6.9 occurred 8 km north of Samos Island at a depth of 16 km on 30.10.2020, at 11:51:24 UTC (14:51:24 Local Time (LT)). It occurred on a 40-kilometer-long north-dipping normal fault zone in the Mediterranean between Greece's Samos Island and Turkey's Kusadasi Bay. Following the mainschock, a tsunami with a height of more than 1 meter occurred at Sigacik Bay, south of Izmir, and on the north side of Samos Island. This article focuses on the investigation of the Samos earthquake by utilizing both GNSS data and InSAR images, and the obtained results are given in this paper. GNSS data were processed by using CSRS-PPP Software as static and kinematic modes. After processing the GNSS data, the maximum displacements were observed at CESME and IZMIR CORS-TR points located in the north of the fault. Horizontal movements of 12 cm and 6 cm towards the north were obtained at CESME and IZMIR points, respectively. However, the amount of horizontal movements was less at DIDIM and AYDIN CORS-TR locations, which are located to the south of the fault. In addition to GNSS data, ESA Sentinel-1 SAR data was used in the InSAR procedure, and the displacements were clarified using the unwrapped interferogram. The interferogram revealed a 10 cm uplift in the west of the Island of Samos and a 10 cm subsidence in the Izmir region, on the north side of the fault, based on the InSAR data. The most striking feature of this study is that the earthquake that occurred near the island of Samos was reported by Gansas' study that the 3 GNSS points (SAMO, SAMU, and 093A) on the island of Samos are moving in a south direction and the largest displacement is about 36 centimetres south. However, in our study, the north direction is more prominent as the direction of movement at IZMIR and CESME points. The movement at the DIDIM point supports his work. In other words, the Samos Fault affected the points located in the north and south differently.
Keywords: 2020 Samos earthquake; CORS; InSAR; GNSS; Deformation; SOUTH; FIELD; MODEL; SLIP; Engineering